Modern literature and the tragic - Newton, Kenneth M. (Edinburgh University Press, 2008)
This book explores modern literature's responses to the tragic. Although Ibsen has been accused of being responsible for the 'death of tragedy', Ken Newton argues that Ibsen instead generated an anti-tragic perspective that had a major influence on dramatists such as Shaw and Brecht